NILAI THEOLOGIS DALAM SERAT WEDHATAMA - -, Purwadi (Diksi, 2015)
Serat Wedhatama is a Javanese literary work by Sri Mangkunegara IV. It contains considerable piwulang luhur (or valuable teachings) in the ethics of life in social interaction. This article concerns a research aiming at describing the theological values in Serat Wedhatama which are often referred to as Sembah Raga, Sembah Cipta, Sembah Jiwa, and Sembah Rasa. They are said to coincide with what are usually referred to in Moslem sufism as syariat, tarikat, hakikat, and makrifat as well as with what are always referred to in Hinduism as artha, kama, dharma, and muksa. In that work of his, Sri Mangkunegara IV is able to make a successful discourse of harmony among traditional Javanese principles, Islamic principles, and Hindu principles. Serat Wedhatama could thus become important reading for Javanese people. Keywords : theology, Serat Wedhatama, ethics of life